2016 IEEE 16th International Conference on Advanced Learning Technologies (ICALT) 2016
DOI: 10.1109/icalt.2016.119
|View full text |Cite
|
Sign up to set email alerts
|

Supporting Users of Open Online Courses with Recommendations: An Algorithmic Study

Abstract: Abstract-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…In terms of RSs that use the collaborative approach, they are thought to evidence the cold-start problem, with works [36,41,56] suggesting a greater volume of data to improve performance, and [22,48] adding more parameters to the user profile, such as learning styles or reading tastes-in general, it is suggested that this be combined with other approaches in order to improve performance. Ref.…”
Section: Discussionmentioning
confidence: 99%
“…In terms of RSs that use the collaborative approach, they are thought to evidence the cold-start problem, with works [36,41,56] suggesting a greater volume of data to improve performance, and [22,48] adding more parameters to the user profile, such as learning styles or reading tastes-in general, it is suggested that this be combined with other approaches in order to improve performance. Ref.…”
Section: Discussionmentioning
confidence: 99%
“…Even if the information is found, it may not be the solution to the real cause of the problem; moreover, it may not be completely understood because the basics are not complete. For students who are just beginning, this may cause a confidence blow, and reduce their willingness to learn (Fazeli et al, 2016;Long, 2016). Therefore, through the Bayesian classifier, the points that will potentially cause problems among the entire learning data set are classified, labels and weights are set to determine the possible probabilities of the causes of the problems encountered by the students, and the probability and weight are used to determine the ultimate causes of the problems.…”
Section: Bayesian Algorithmmentioning
confidence: 99%
“…For instance, to calculate the sub-similarity "how to learn" between users, we consider the vectors of both users in the Boolean user-LO matrix and compute the similarity using the Jaccard coefficient. We use this coefficient because the matrix is the same of the user-item rating matrix in the User-based Nearest Neighbor recommendation approach, and [Fazeli et al 2016] showed that this measure is better for LO recommendation over implicit feedback. In Subsection 4.2, we define how to compute each sub-similarity in the MERLOT e-learning platform.…”
Section: A) Multidimensional User Preference Modelmentioning
confidence: 99%